PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING YANG DIAWALI TUGAS MERINGKAS TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMAN 2 SUTERA KABUPATEN PESISIR SELATAN TAHUN PELAJARAN 2013/2014 - Astuti, Wiwit - (Pendidikan Biologi, 2014)
The low learning result of biology students at SMAN 2 Sutera Kabupaten Pesisir Selatan because students tend to passive during the learning process. The students have less attention and also courage to ask about the material that less understood. This requires teachers to select an appropriate learning model. This study aims to determine the effect of cooperative learning model with Snowball Throwing type begins with summarize task toward the learning outcome of biology class students at X SMAN 2 Kabupaten Pesisir Selatan in year 2013/2014. The research is an experimental research with randomized control group postest only design. The study population was all students of class X SMAN 2 Kabupaten Pesisir Selatan in year 2013/2014, consist of four classes. The sampling technique is by using purposive sampling, which pay attention to classes who have the same average value. So, it is selected X1 as experiment class and X2 class as the control class. The average results of the student tests for experiment class is 79,50 and 70.58 for the control class. Based on the results of hypothesis testing using t-test obtained t > t table is 1.74 > 1.66 . It means that the hypothesis of this study received and it can be inferred that by applying cooperative learning model Snowball Throwing type can increase the result of students biologyâs learning at X grade students at SMAN 2 Kabupaten Pesisir Selatan year 2013/2014. This learning model can also improve student affective, because the student can interact in groups and also with the teacher. However, the summarizing task that is used as a psychomotor assessment does not give effect to student learning outcomes.